Pendampingan Pemanfaatan Teknologi Informasi dalam Pembuatan Modul Elektronik di SMAN 17 Lamuru Kabupaten Bone - Muh. Alwi; Risnashari Risnashari; Juhardi Juhardi; Kusmaladewi Kusmaladewi; Jamil Jamil; Sitti Wahidah Masnani; Andi Agussalim (Institut Nalanda, 2026)
The enhancement of teachers' digital competence is a strategic issue directly impacting the success of digital transformation in schools. The partner of this community service, SMAN 17 Lamuru in Bone Regency, faced constraints regarding limited digital literacy and technostress in producing independent interactive teaching materials. This program aimed to improve teachers' digital competence in developing electronic modules (e-modules) through a structured mentoring program. The execution method utilized a Blended Workshop and Coaching model based on a participatory learning approach involving 30 subject teachers. The offline intervention was conducted over two days through a combination of lecturing, live demonstration, guided practice, and Focus Group Discussions (FGD), followed by three weeks of independent mentoring. Evaluation instruments included performance observation sheets, satisfaction questionnaires, and capability tests using a 1–100 assessment scale. Data were analyzed using the parametric paired samples t-test. The statistical results indicated a highly significant improvement, where the teachers' mean score surged from 55.50 during the pretest to 83.50 in the posttest session, yielding a t-value of 34.293 with a coefficient of Sig. (2-tailed) = 0.000 < 0.05. The guided participatory approach proved effective in reducing the digital divide classically and fostering teachers' self-efficacy. The program concludes that this mentoring successfully produced valid subject e-modules ready to be implemented to support a student-centered learning ecosystem.